CONTEXTUAL TEACHING AND LEARNING ( CTL) DAN PENGARUHNYA TERHADAP HASIL BELAJAR MATEMATIKA MAHASISWA - Ika Ratih Sulistiani (Universitas Islam Malang, 2020)
The research carried out on PGMI Unisma students aims to find out the differences between student mathematics learning outcomes using the Contextual Teaching and Learning learning model and the Expository Learning model. This study involved 44 students in which 22 students were in the experimental group and 22 students were in the control group. This research is a kind of experimental research. Data collection techniques used are documentation and tests. Homogeneity and normality tests are the main requirements before researchers conduct hypothesis testing. The output from the t test shows Sig. (2 - tailed) of 0.003 <0.005, it can be concluded that H0 is rejected and H1 is accepted. So it can be concluded that there is a significant) difference between the average mathematics learning outcomes of CTL and Expository class studentsThe research carried out on PGMI Unisma students aims to find out the differences between student mathematics learning outcomes using the Contextual Teaching and Learning learning model and the Expository Learning model. This study involved 44 students in which 22 students were in the experimental group and 22 students were in the control group. This research is a kind of experimental research. Data collection techniques used are documentation and tests. Homogeneity and normality tests are the main requirements before researchers conduct hypothesis testing. The output from the t test shows Sig. (2 - tailed) of 0.003 <0.005, it can be concluded that H0 is rejected and H1 is accepted. So it can be concluded that there is a significant) difference between the average mathematics learning outcomes of CTL and Expository class students